Impact of gas spin and Lyman-Werner flux on black hole seed formation in cosmological simulations: implications for direct collapse - Bhowmick, Aklant; Blecha, Laura; Torrey, Paul; Kelley, Luke Zoltan; Vogelsberger, Mark; Nelson, Dylan; Weinberger, Rainer; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2022)
Direct collapse black holes (BHs) are promising candidates for producing massive z ≳ 6 quasars, but their formation requires fine-tuned conditions. In this work, we use cosmological zoom simulations to study systematically the impact of requiring: (1) low gas angular momentum (spin), and (2) a minimum incident Lyman-Werner (LW) flux in order to form BH seeds. We probe the formation of seeds (with initial masses of $M_{\rm seed} \sim 10^4\!-\!10^6\, M_{\odot }\, h^{-1})$ in haloes with a total mass >3000 × Mseed and a dense, metal-poor gas mass >5 × Mseed. Within this framework, we find that the seed-forming haloes have a prior history of star formation and metal enrichment, but they also contain pockets of dense, metal-poor gas. When seeding is further restricted to haloes with low gas spins, the number of seeds formed is suppressed by factors of ∼6 compared to the baseline model, regardless of the seed mass. Seed formation is much more strongly impacted if the dense, metal-poor gas is required to have a critical LW flux (Jcrit). Even for Jcrit values as low as 50J21, no $8× 10^{5}~M_{\odot }\, h^{-1}$ seeds are formed. While lower mass ($1.25× 10^{4},1× 10^{5}~M_{\odot }\, h^{-1}$) seeds do form, they are strongly suppressed (by factors of ∼10-100) compared to the baseline model at gas mass resolutions of $\sim 10^4~M_{\odot }\, h^{-1}$ (with even stronger suppression at higher resolutions). As a result, BH merger rates are also similarly suppressed. Since early BH growth is dominated by mergers in our models, none of the seeds are able to grow to the supermassive regime ($\gtrsim 10^6~M_{\odot }\, h^{-1}$) by z = 7. Our results hint that producing the bulk of the z ≳ 6 supermassive BH population may require alternate seeding scenarios that do not depend on the LW flux, early BH growth dominated by rapid or super-Eddington accretion, or a combination of these possibilities.
Advance access publication 2021 November 27
Gesehen am 20.04.2022